Representação social do trabalho em equipe no programa de internação domiciliar e suas repercussões no cuidado integral - Ponte, Lidiane Cola Roceti Dal (2010)
Given the speed of the changes occurring in the political, economic, social, cultural and technological organizations in healthcare are seeking new standards for work processes and forms of administrations to respond effectively and fully the needs of workers and users. The home becomes a space that seeks to build a new logic of attention centered on the humane care. Thus, this research aimed to analyze the social representations about the teamwork of healthcare professionals from a home care program for caregivers and accompanied by the same program. This is an exploratory study that consisted of a first stage of the bibliography of publications in the Medline and Scielo base, and the second phase of participant observation and interviews with professionals who comprise the team of the Interdisciplinary Program of home care and carers together the program in the city of Marilia. It was used for data systematization ALCESTE 4.5 software and the analysis of categories occurred in the Theory of Social Representations. Teamwork for both team members, and for carers is in a range of professional groups working in the same apace, but each in their specific area.Thus, it is clear that the process of fragmented work performed by professionals, and conducts individual behaviors are the result of such representation on teamwork, ie the type grouping. These attitudes and actions come to produce care practices focus on medicalhegemonic models that are part of daily life of caregivers, helping them build their representations on teamwork also of type grouping.